2015
DOI: 10.2989/16073606.2015.1026559
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of predator-prey models with refuge, harvesting and dispersal

Abstract: The dynamics of predator-prey models with different prey harvesting functions and prey refuge is studied. This study includes a three-dimensional model to account for the dispersal of prey to a habitat where it is unavailable to the predator. Besides local stability analysis, one central question is how harvesting, refuge and dispersal could directly affect the dynamics of the ecosystem, such as existence and dynamics of coexistence equilibria and periodic solutions. Theoretical and numerical methods are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The study also revealed that bold but less vigilant prey remained in the open habitat at the expense of their stock, while more apprehensive and less vigilant prey chose the refuge, compromising their foraging and mating opportunities. Some prior studies, [20][21][22] examined different aspects of prey-predator dynamics incorporating various factors such as time delay, refuge, harvesting, and prey dispersal. Alidousti and Ghahfarokhi [20] focused on a time-delay fractional predator-prey system with prey dispersal and demonstrated that the fractional system exhibited periodic solutions with shorter periods compared to the classical case, expanding the stability domain under the fractional order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also revealed that bold but less vigilant prey remained in the open habitat at the expense of their stock, while more apprehensive and less vigilant prey chose the refuge, compromising their foraging and mating opportunities. Some prior studies, [20][21][22] examined different aspects of prey-predator dynamics incorporating various factors such as time delay, refuge, harvesting, and prey dispersal. Alidousti and Ghahfarokhi [20] focused on a time-delay fractional predator-prey system with prey dispersal and demonstrated that the fractional system exhibited periodic solutions with shorter periods compared to the classical case, expanding the stability domain under the fractional order.…”
Section: Introductionmentioning
confidence: 99%
“…Alidousti and Ghahfarokhi [20] focused on a time-delay fractional predator-prey system with prey dispersal and demonstrated that the fractional system exhibited periodic solutions with shorter periods compared to the classical case, expanding the stability domain under the fractional order. In contrast, Hare and Rebaza [21] investigated the dynamics of a predator-prey system with refuge, harvesting, and dispersal. They introduced two patches in a three-dimensional model to represent unavailable prey habitat and a classical predator-prey relationship, including refuge and harvesting.…”
Section: Introductionmentioning
confidence: 99%